2019
DOI: 10.18633/biotecnia.v21i3.1012
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of nutritional and nutraceutical value of nixtamalized maize tortillas by addition of extruded chia flour

Abstract: In this work the objectives were: (1) To optimize the extrusion conditions of defatted chia seeds maximizing antioxidant activity (AoxA), total phenolic content (TPC) and in vitro protein digestibility (IVPD), and (2) To evaluate the nutritional, nutraceutical, and sensory (acceptability) properties of tortillas formulated with commercial nixtamalized maize flour (MASECAMR) and optimized extruded defatted chia flour. Response surface methodology was applied as an optimization tool. A central composite rotatabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 32 publications
4
19
0
Order By: Relevance
“…The IC 50 values found for phenolic extracts of optimized ExtCP flour in this study agree with the results reported for extruded defatted chia seeds (León‐López et al, 2019). An improvement in the IC 50 value by extrusion process application to chickpea was observed in this study (IC 50 value to raw chickpea was not reported); the improvement could be attributed to the release and forming of bioactive compounds (phenolic compounds and MRP) with antihypertensive potential.…”
Section: Resultssupporting
confidence: 92%
“…The IC 50 values found for phenolic extracts of optimized ExtCP flour in this study agree with the results reported for extruded defatted chia seeds (León‐López et al, 2019). An improvement in the IC 50 value by extrusion process application to chickpea was observed in this study (IC 50 value to raw chickpea was not reported); the improvement could be attributed to the release and forming of bioactive compounds (phenolic compounds and MRP) with antihypertensive potential.…”
Section: Resultssupporting
confidence: 92%
“…The phenolic compounds extracted from ECBMF and EAF had potential antihypertensive activity with IC 50 of 0.49 and 0.40 mg extract/mL, respectively, while the phenolic extracts from blue MASECA TM flour had an IC 50 =2.51 mg extract/mL (Table 2). The benefits of the IC 50 obtained in this research are in concordance with reported results for phenolic extracts from soybean (0.143-0.160 mg/ mL), and unprocessed and extruded defatted chia seeds (0.35-0.51 mg/mL) (Ademiluyi and Oboh, 2013;León-López et al, 2019). The improvement of IC 50 values during the extrusion process of creole blue maize and amaranth seeds could have occurred by the release and formation of bioactive compounds (phenolic compounds and MRP) with antihypertensive potential.…”
Section: Antihypertensive and Hypoglycemic Potentials Of Phenolic Compounds Extracted From Extruded Grain Flourssupporting
confidence: 91%
“…The nixtamalization process to prepare tortillas presents problems of high liquid waste discharges. Extrusion, an alternative to nixtamalization, does not generate polluting effluents, and all the components of the grain, including the pericarp, are retained, producing a tortilla with higher fiber content (Milán-Carrillo et al, 2006;Escalante-Aburto et al, 2013;León-López et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the seed has highly soluble and insoluble dietary fiber, over 35% of the total weight, and a rich source of the B vitamins and minerals. It also contains six more-fold calcium, 11 morefold phosphorus, and four more-fold potassium than 100 g of milk; besides this, it possesses magnesium, iron, zinc, and copper (León-López et al, 2019;Masood, 2022;Orona-Tamayo et al, 2017). On top of that, it has many natural antioxidants, such as phenolic compounds (chlorogenic and caffeic acids, and flavonols [quercetin, kaempferol, myricetin]), which protect against some adverse conditions (Hrncic et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…These accelerate process conditions, used during the extrusion, cause important molecular transformation and chemical reactions (modification in starch, proteins, dietary fiber and lipids, inactivation of enzymes and microorganisms, and formation of color polymers and volatile flavor components) on the food materials. In addition, this process is a highly efficient alternative technology that minimizes energy and water consumption, and does not produce polluting effluents (León-López et al, 2019;Ortiz-Cruz et al, 2020;Ramos-Enríquez et al, 2018;Reyes-Moreno et al, 2018).…”
Section: Introductionmentioning
confidence: 99%